(untitled) (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon our master Muhammad and his family and companions, and afterThe Islamic call suffers in the present age from a clear state of weakness after the forces of evil have allied themselves.The darkness is against this religion and helped to increase this weakness, the ignorance of many Muslims of the importance of the meansThe modern communication of the Islamic call, which led to the failure to use these means in an optimal way.With the aim of calling to Islam and informing people of this religion, which is a mercy for workers.The satellite channels, which penetrated the barriers and borders, and their broadcasts reached every place in thisThe world - one of the most important modern means of communication that can be invested in the call to the religion of Islam and the mediaMuslims everywhere in this world to the contents of this religion and make them aware of the matters of their religion.And based on the importance of satellite channels for the Islamic call, this research came to address the callIslamic satellite channels, using the Iqar Islamic satellite channel as a case study as a subject for this study.search. The researcher defined the Islamic call and defined the forms and templates of television materials adopted inMost of the TV channels to access the formats and templates used in the Iqr satellite channelThis research is considered one of the descriptive researches that use the survey method, with the help of a questionnaireAnalysis as a research tool for analyzing and collecting information related to the phenomenon in order to reach conclusions.and indications that the research aims to.The researcher identified a community that he researched in the television materials shown on the Iqr satellite channel, and choseAn intentional sample for a full week, which I subject to analysis through a comprehensive sample survey.The researcher encountered some difficulties while writing the research and defining the sample.which the city of Fallujah witnessed after it was subjected to a comprehensive attack by the US Marines in8/11/2004 and the displacement of its people, including the researcher and his family, and the destruction that followed the invasion.complete destruction of the city of Fallujah and the disruption of electricity, telephone and Internet services, and what these events left ofA psychological impact on the researcher that made him delay a bit in completing this research. The researcher divided thisThe research was divided into three chapters, the first chapter of which was devoted to the methodological framework of the research.